2015
DOI: 10.1021/acs.joc.5b01518
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Free Oxidative Radical Decarboxylation/Cyclization for the Construction of 6-Alkyl/Aryl Phenanthridines

Abstract: A radical cascade decarboxylation/cyclization of 2-isocyanobiphenyls with aliphatic carboxylic acids as well as aromatic carboxylic acids under the transition metal-free conditions was reported. This process, which included formation of two new C-C bonds and cleavage of C-COOH bonds, afforded a novel and environmentally friendly approach to producing 6-alkyl/aryl phenanthridines with moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 45 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Simultaneously, Lu and co-workers reported a transition-metal-free synthesis of the trifluoromethylphenanthridine 79a in 58% yield using the system CF 3 SO 2 Na/K 2 S 2 O 8 /K 2 CO 3 in H 2 O/CH 3 CN at 80 °C [ 90 ]. In addition, Maruoka and co-workers used the system CF 3 SO 2 Na/PIFA/AcONa in AcOEt at room temperature for 1.5 h to get 79a in 74% yield [ 50 ].…”
Section: Reviewmentioning
confidence: 99%
“…Simultaneously, Lu and co-workers reported a transition-metal-free synthesis of the trifluoromethylphenanthridine 79a in 58% yield using the system CF 3 SO 2 Na/K 2 S 2 O 8 /K 2 CO 3 in H 2 O/CH 3 CN at 80 °C [ 90 ]. In addition, Maruoka and co-workers used the system CF 3 SO 2 Na/PIFA/AcONa in AcOEt at room temperature for 1.5 h to get 79a in 74% yield [ 50 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, Xu and co-workers 12 reported a facile approach to introduce an all-carbon quaternary center containing a CF 3 functionality via oxidative dicarboxylative 1,1dimethyltrifluoroethylation of quinoxalin-2(1H)-ones using 3,3,3-trifluoro-2,2-dimethylpropanoic acid as the radical precursor. Among the different oxidants screened, ammonium persulfate was found to be the most effective for this…”
Section: Reactions With Alkyl Radicalsmentioning
confidence: 99%
“…Based on a previous report, 13 Xu et al 12 proposed the following mechanism (Scheme 7). 3,3,3-Trifluoro-2,2-dimethylpropanoic acid is oxidized by ammonium persulfate to furnish a C(CH 3 ) 2 CF 3 radical, which then adds to the quinoxalin-2(1H)-one to afford N-centered radical species 6.…”
Section: Scheme 6 Substrate Scope For the Direct C3 Trifluoroalkylatimentioning
confidence: 99%
“…However, the Lu group found that silver is not necessary for the oxidative radical decarboxylation/cyclization for the construction of 6-alkylphenanthridines from 2-isocyanobiphenyls (Scheme 6). 19 Under transition-metal-free conditions, alkylcarboxylic acids reacted with 2-isocyanobiphenyls and afforded the desired products in good yields. A mechanism without a silver catalyst is proposed.…”
Section: Syn Thesis Scheme 5 Silver-mediated Alkylation Of Benzothiazmentioning
confidence: 99%